Exploring Novel Fungal–Bacterial Consortia for Enhanced Petroleum Hydrocarbon Degradation - João Paulo Silva Monteiro; André Felipe da Silva; Rubens Tadeu Delgado Duarte; Admir José Giachini (Toxics, 2024)
Bioremediation, involving the strategic use of microorganisms, has proven to be a cost-effective alternative for restoring areas impacted by persistent contaminants such as polycyclic aromatic hydrocarbons (PAHs). In this context, the aim of this study was to explore hydrocarbon-degrading microbial consortia by prospecting native species from soils contaminated with blends of diesel and biodiesel (20% biodiesel/80% diesel). After enrichment in a minimal medium containing diesel oil as the sole carbon source and based on 16S rRNA, Calmodulin and β-tubulin gene sequencing, seven fungi and 12 bacteria were identified. The drop collapse test indicated that all fungal and four bacterial strains were capable of producing biosurfactants with a surface tension reduction of ≥20%. Quantitative analysis of extracellular laccase production revealed superior enzyme activity among the bacterial strains, particularly for Stenotrophomonas maltophilia P05R11. Following antagonistic testing, four compatible consortia were formulated. The degradation analysis of PAHs and TPH (C5–C40) present in diesel oil revealed a significantly higher degradation capacity for the consortia compared to isolated strains. The best results were observed for a mixed bacterial-fungal consortium, composed of Trichoderma koningiopsis P05R2, Serratia marcescens P10R19 and Burkholderia cepacia P05R9, with a degradation spectrum of ≥91% for all eleven PAHs analyzed, removing 93.61% of total PAHs, and 93.52% of TPH (C5–C40). Furthermore, this study presents the first report of T. koningiopsis as a candidate for bioremediation of petroleum hydrocarbons.